Court and cosmos : the great age of the Seljuqs - Canby, Sheila R.; Beyazit, Deniz; Rugiadi, Martina; Peacock, A. C. S.; Metropolitan Museum of Art (New York, N.Y.) (New York : Metropolitan Museum of Art, 2016)
"The powerful and culturally prolific Seljuqs--an empire whose reach extended from Central Asia to the eastern Mediterranean--dominated the Islamic world from the eleventh to the fourteenth century. The age of the Seljuqs was one that celebrated magnificence, in this world and the celestial realm. Court and Cosmos: The Great Age of the Seljuqs examines the roots and impact of this dynasty, featuring some 250 objects as evidence of the artistic and cultural flowering that occurred under Seljuq rule, and providing an invaluable record of the Seljuqs' contribution to the cultural heritage of the Islamic world." -- Publisher's description
Catalog of the exhibition held at the Metropolitan Museum of Art, New York, April 27-July 24, 2016.
Includes bibliographical references (pages 336-354) and index.
Keywords: Seldschuken; Art, Seljuk -- Exhibitions; Seljuks -- Civilization -- Exhibitions; Art, Seljuk; Seljuks; Sachkultur; Volkskunst; Exhibition catalogs; History